PENGEMBANGAN MEDIA PAPAN PINTAR ANGKA UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF BAGI ANAK KELOMPOK B - Azalia Rizkini Pratiwi; Ika Rachmayani; Nurhasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study is to produce a smart number board media to develop the ability to recognize numbers in early childhood. The research was conducted at Nurul Iman Kindergarten, Central Lombok. This study used the Research and Development (R&D) method with the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were 21 children in group B. Data collection techniques included observation and documentation, and the data analysis technique was descriptive quantitative. The developed product was a smart number board media that has been validated by media and material experts. The development of the smart number board media to improve children's cognitive abilities achieved an 88.8% feasibility percentage, categorizing it as very suitable for use.  The steps for using the smart number board media are as follows: 1) Form groups first, 2) Then the teacher instructs the children to roll the dice according to the number of dots rolled, 3) If the dice show 3, the child will take an instruction card from pocket number 3, 4) The child then follows the instructions received. The results of the study on improving the cognitive abilities of group B children after learning with the smart number board media from development stages I, II, and III showed progress. The average cognitive ability in development stage I was 33%, categorized as starting to develop; in development stage II, it increased to 72%, categorized as developing as expected; and in development stage III, it reached an average of 88%, categorized as developing very well. These results indicate that the smart number board media is suitable for use as a learning medium in Nurul Iman Kindergarten, Central Lombok.